Development and Applications of Chromosome-Specific Cytogenetic BAC-FISH Probes in S. spontaneum - Dong, Guangrui; Shen, Jiao; Zhang, Qing; Wang, Jianping; Yu, Qingyi; Ming, Ray; Wang, Kai; Zhang, Jisen (Frontiers in Plant Science, 2018)
Saccharum spontaneum is a major Saccahrum species that contributed to the origin of modern sugarcane cultivars, and is considered to be a plant species with one of the most complex genetics due to a high degree of polyploidy. Fluorescence in situ hybridization is a powerful and widely used tool in the genome studies. Here we demonstrated that fluorescence in situ hybridization (FISH) based on bacterial artificial chromosome (BAC) clones can be used as a specific cytological marker to identify S.spontaneum individual chromosomes and study the relationship between S.spontaneum and other related species. We screened low-copy BACs as probes from the sequences of a high coverage of S. spontaneum BAC library based on BLAST search of the sorghum genome. In total, we isolated 49 positive BAC clones, and identified 27 BAC clones that can give specific signals on the S.spontaneum chromosomes. Of the 27 BAC probes, 18 were confirmed to be able to discriminate the eight basic chromosomes of S.spontaneum. Moreover, BAC-24, BAC-66, BAC-78, BAC-69; BAC-71, BAC-73 and BAC-77 probes were used to construct chromosome 1 and chromosome 2 physical mapping of S. spontaneum, indicating synteny in Sb01 between S.spontaneum and sorghum. Furthermore, we found that BAC-14 and BAC-19 probes, corresponding to the sorghum chromosomes 2 and 8, respectively, localized to different arms of the same S.spontaneum chromosome, suggesting that there must have been an inter-chromosomal rearrangement event between S. spontaneum and sorghum. Our study provided the first set of chromosome-specific cytogenetic makers in Saccharum, and is critical for future advances in cytogenetics and genome sequencing studies in Saccharum.